THE USE OF CARD TRICK TO BUILD STUDENTS’ VOCABULARY - Eny Dwi Marcela (International Conference on Education and Language (ICEL), 2016)
Language teachers have been told a great deal about new discoveries in English grammar, but they have heard much less about ways to help students learn new words. As an English teacher who had to perform in front of the class with fresh ideas, card tricks turned out to be a brilliant idea, especially when you have to teach new vocabulary to students. The purpose of this study is to determine the strategies that support and enhance students' understanding of new vocabulary and to help students remember their English vocabulary by teaching in a fun strategy.